Foreign Aid and Economic Growth: An Econometric Study of Afghanistan - Fazlly, Sayed Kifayatullah (Journal of Indonesian Applied Economics, 2024)
Purpose This study aims to investigate the impact of foreign aid on economic growth in Afghanistan. Design/methodology/approach The study employs various econometric techniques, including time series analysis. Data for the study are sourced from the country economy and world development indicators of the World Bank, covering the period from 1980 to 2021. The analysis includes Augmented Dicky Fuller and Phillips Perron unit root tests, the ARDL model, the Breusch-Godfrey Serial Correlation LM Test, and the ARDL bounds test. Findings The economic growth series is found to be level stationary, while the net official development assistance series is first difference stationary. Net official development assistance exhibits a significant positive short-run relationship with economic growth. No serial correlation is observed between net official development assistance and economic growth. Net official development assistance demonstrates a significant positive long-run relationship with economic growth. Research limitations/implications The study is based on data up to 2021, which may not capture recent developments or changes in the relationship between foreign aid and economic growth. The analysis relies on the accuracy and reliability of the data provided by the World Bank and other sources. Originality/value This study contributes empirical evidence on foreign aid's impact on economic growth in Afghanistan, using a range of econometric techniques. The findings highlight the importance of donor-friendly policies to increase development assistance to Afghanistan.